2015
DOI: 10.1016/j.compedu.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of pupil, classroom and school level characteristics to primary school pupils' ICT competences: A performance-based approach

Abstract: The central aim of this study was to investigate which pupil, classroom and school level characteristics are related to primary school pupils' actual ICT competences. A sample of 378 pupils in 58 schools in Flanders (the Dutch speaking part of Belgium) completed a performance-based ICT competence test in order to measure their actual proficiency in retrieving and processing digital information, and in communicating through a computer. To gather information on the factors at each different level, questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 58 publications
(62 reference statements)
4
37
0
Order By: Relevance
“…These results have led us to conclude that there is only one underlying reason which can explain the fact that education environmental tools are practically unknown to Teaching Degree students, bearing in mind that the initial training of newly admitted students to the College is being researchedi.e., the training received in their earlier stages of education needs to be assessed-given, it would seem, that such tools are not used by Primary and Secondary/High School teachers as part of teaching content in the classroom (see also Gallego & Alonso, 2000, Van Braak, Tondeur & Valcke, 2004Sime & Priestley, 2005;Drent & Meelissen, 2008;Leask & Pachler, 2013;Hammond, 2014;Aesaert, Van Nijlen, Vanderlinde, Tondeur, Devlieger & van Braak, 2015).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…These results have led us to conclude that there is only one underlying reason which can explain the fact that education environmental tools are practically unknown to Teaching Degree students, bearing in mind that the initial training of newly admitted students to the College is being researchedi.e., the training received in their earlier stages of education needs to be assessed-given, it would seem, that such tools are not used by Primary and Secondary/High School teachers as part of teaching content in the classroom (see also Gallego & Alonso, 2000, Van Braak, Tondeur & Valcke, 2004Sime & Priestley, 2005;Drent & Meelissen, 2008;Leask & Pachler, 2013;Hammond, 2014;Aesaert, Van Nijlen, Vanderlinde, Tondeur, Devlieger & van Braak, 2015).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Use of the Internet or digital devices at home is a vital factor influencing primary students' ICT literacy [13]. Specifically, a study in German primary schools suggested a lack of parental concern for the online behaviors of their children from lower socioeconomic backgrounds [14].…”
Section: Potential Research Questionsmentioning
confidence: 99%
“…The integration of ICTs into primary education training processes continues to face major challenges because the effectiveness of ICT use in the classroom depends on several factors: a) adequate functioning of available digital computing resources, connectivity and Internet access (Trigueros, Sánchez and Vera, 2012;Necuzzi, 2013;Santiago, Caballero, Gómez and Domínguez, 2013;Sunkel, Trucco and Espejo, 2014); b) the skills and abilities of all those involved in the training process, that is to say, the digital skills of students (Claro, 2010;Trigueros et al, 2012;Aesaert, Van Nijlen, Vanderlinde, Tondeur, Devlieger and van Braak, 2015;Fajardo, Villalta and Salmerón, 2016); c) pedagogical practices that encourage the interaction of students with ICTs are required (Saez, 2012;Necuzzi, 2013;Santiago et al, 2013;, 2015); and d) lack of leadership or policies that encourage the use of ICT in the classroom (de Pablos, 2009;Hadjithoma and Karagiorgi, 2009;Claro, 2010;Ulate, 2013;Díaz-Barriga, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%